2020
DOI: 10.14309/ajg.0000000000000749
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotics for Celiac Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: INTRODUCTION: Many patients with celiac disease (CD) experience persistent symptoms despite adhering to the gluten-free diet. Different studies have assessed the use of probiotics as an adjuvant treatment for CD. We performed a systematic review and meta-analysis to evaluate the efficacy of probiotics in improving gastrointestinal (GI) symptoms and quality of life (QOL) in patients with CD. METHODS: We searched EMBASE, MEDLINE, CINAHL, Web of Science, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 27 publications
0
24
0
7
Order By: Relevance
“…Although yet unproven, Lactobacillus and Bifidobacterium show promise in a variety of disorders through suppressing growth or invasion of pathogenic bacteria, improving intestinal barrier function, and modulating the immune system [ 77 , 78 , 79 , 80 ]. According to Gurung et al, both are among bacteria negatively associated with T2D together with Akkermansia , Bacteroides , Faecalibacterium , and Roseburia [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although yet unproven, Lactobacillus and Bifidobacterium show promise in a variety of disorders through suppressing growth or invasion of pathogenic bacteria, improving intestinal barrier function, and modulating the immune system [ 77 , 78 , 79 , 80 ]. According to Gurung et al, both are among bacteria negatively associated with T2D together with Akkermansia , Bacteroides , Faecalibacterium , and Roseburia [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no such case study till date which reports complete recovery of patient from celiac disease after administration of probiotic supplements along with GFD, but there are studies which indicate the positive prospects of probiotics in CD. [7][8][9] Primec et al in 2018 performed a double-blind placebo-controlled trial on 40 CD and 16 healthy children. CD patients were randomized to receive a mixture of two Bifidobacterium breve strains (DSM 16604 and DSM 24706) or placebo for a period of three months.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of this approach was recently addressed in a meta-analysis that concluded that although probiotics may improve gastrointestinal symptoms in patients with CeD, there is significant heterogeneity between studies and high-quality clinical trials are needed to provide better evidence. 110 Thus, next-generation probiotics should be designed that target specific mechanisms in CeD pathophysiology. These therapies, specifically targeting pathogenic mechanisms or microbial alterations of interest in CeD, should be tested not only for better control of symptoms in patients who are nonresponders to the GFD, but also in primary prevention in at-risk individuals.…”
Section: Role Of the Microbiota And Microbial Metabolitesmentioning
confidence: 99%